Analisis Kemampuan Pemahaman Konsep Matematika Siswa Pada Materi Bangun Datar Kelas IIDi MIS Islamiyah Sunggal Kota Medan - Adisti Yulia Putri; Astria Ayu Ramadianti; Syarifah Ainun Harahap (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
Conceptual understanding ability is the most basic ability that is very necessary for students in mastering learning materials. Based on initial observations in class II MIS Islamiyah Sunggal, it shows that students' conceptual understanding ability in flat shape material is still relatively low. The purpose of this study is to analyze students' conceptual understanding ability in flat shape material in class II MIS Islamiyah Sunggal. This study is a descriptive qualitative field study. The subjects in this study were students of class II MIS Islamiyah Sunggal. The data collection method used interview, observation and documentation techniques. Data collection was carried out using data reduction techniques, data presentation and drawing conclusions. The results of this study can be concluded that: Students' conceptual understanding ability in learning mathematics on flat shape material for class II at MIS Islamiyah Sunggal, can be categorized as good. Students are able to restate a concept, classify concepts based on their properties, and can give examples of a concept. From the value of students' understanding of flat shape material, the overall percentage has reached 90% of students who have achieved a value above the minimum standard value. Supporting factors in understanding students' concepts are Facilities, Educators, Motivation and good student absorption. While inhibiting factors are Lack of enthusiasm and active learning of students, and Lack of Practice and Habits in Solving Problems.